Death depression in Egyptian clinical and non‐clinical groups. Issue 1 (31st August 2020) - Abdel‐Khalek, Ahmed M.; Dadfar, Mahboubeh; Lester, David
Abstract: Aim: The main aims of this study were to explore the differences between seven Egyptian clinical and non‐clinical samples in death depression, as well as to estimate gender‐related differences. Design: A cross‐sectional study. Methods: The Death Depression Scale (DDS) was administered to seven groups ( N = 765) of Egyptian normal (non‐clinical) patients, anxiety outpatients, schizophrenic inpatients (men and women) and addicts (men only) in individual sessions. Results: Anxiety outpatients of both sexes obtained significantly and greatly higher death depression scores than did the other five groups, whereas the male schizophrenics, the male addicts, and the male and female non‐clinical groups had the lowest death depression scores. Female schizophrenics obtained a significantly higher death depression scores than did male schizophrenics, addicts and non‐clinical participants. Female anxiety outpatients and schizophrenics had higher death depression mean scores than did their male counterparts. Discussion: The present finding is consistent, in general, with previous studies on death anxiety and death obsession. What applied to death anxiety was consistent also with death depression and death obsession. That is, the death distress concept.